Lessons from KEEPS: the Kronos Early Estrogen Prevention Study. (4th March 2021) - Miller, V. M.; Taylor, H. S.; Naftolin, F.; Manson, J. E.; Gleason, C. E.; Brinton, E. A.; Kling, J. M.; Cedars, M. I.; Dowling, N. M.; Kantarci, K.; Harman, S. M.
Abstract: The Kronos Early Estrogen Prevention Study (KEEPS) was a randomized, double-blind, placebo-controlled trial designed to determine the effects of hormone treatments (menopausal hormone treatments [MHTs]) on the progression of carotid intima-medial thickness (CIMT) in recently menopausal women. Participants less than 3 years from menopause and without a history of overt cardiovascular disease (CVD), defined as no clinical CVD events and coronary artery calcium < 50 Agatston units, received either oral conjugated equine estrogens (0.45 mg/day) or transdermal 17β-estradiol (50 µg/day), both with progesterone (200 mg/day for 12 days/month), or placebo pills and patches for 4 years. Although MHT did not decrease the age-related increase in CIMT, KEEPS provided other important insights about MHT effects. Both MHTs versus placebo reduced the severity of menopausal symptoms and maintained bone density, but differed in efficacy regarding mood/anxiety, sleep, sexual function, and deposition of β-amyloid in the brain. Additionally, genetic variants in enzymes for metabolism and uptake of estrogen affected the efficacy of MHT for some aspects of symptom relief. KEEPS provides important information for use of MHT in clinical practice, including type, dose, and mode of delivery of MHT recently after menopause, and how genetic variants in hormone metabolism may affect MHT efficacy on specific outcomes.